2002
DOI: 10.1210/jc.2001-011889
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Bone Mineral Accrual in Adolescent Girls with Anorexia Nervosa

Abstract: Anorexia nervosa (AN) is increasingly common in adolescent girls and occurs at a time of peak bone mass formation. Osteopenia is common in adolescent girls with AN, and in a cross-sectional study, we have reported low bone formation markers in such girls. To determine the impact of chronic undernutrition on bone mineral accrual in contrast to healthy controls, we prospectively measured bone mineral density (BMD) and body composition by dual energy x-ray absorptiometry, bone metabolism markers, and nutritional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
288
1
14

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 316 publications
(317 citation statements)
references
References 42 publications
14
288
1
14
Order By: Relevance
“…Mechanical loading during weight-bearing activities stimulates bone formation, and multiple studies in healthy adolescents 8,[71][72][73] and in those with anorexia nervosa [74][75][76][77] have demonstrated that BMD is directly correlated with BMI. Lean body mass is most strongly associated with BMD, 78 but increased adiposity can also be associated with increased fracture risk.…”
Section: Body Weightmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanical loading during weight-bearing activities stimulates bone formation, and multiple studies in healthy adolescents 8,[71][72][73] and in those with anorexia nervosa [74][75][76][77] have demonstrated that BMD is directly correlated with BMI. Lean body mass is most strongly associated with BMD, 78 but increased adiposity can also be associated with increased fracture risk.…”
Section: Body Weightmentioning
confidence: 99%
“…84 Eating disorders are prevalent in adolescents. 85 Anorexia nervosa is associated with reduced BMD and increased fracture risk, [74][75][76][86][87][88][89] and the reduction in bone mass occurs after a relatively short duration of illness. 74,90 Etiologic factors include poor nutrition, low body weight, estrogen deficiency, and hypercortisolism.…”
Section: Secondary Prevention: Assessment Of Populations At Risk For mentioning
confidence: 99%
“…36 Low BMD among children may not indicate accelerated bone loss 41 but rather a failure to achieve the expected peak bone mass, bone loss or a combination of the two. 78,79 It is important to acknowledge that the use of antiresorptive drugs, such as bisphosphonates, may not be the optimal approach. Therefore, an understanding of the pathogenesis of low bone mass in paediatric patients with SB is needed.…”
Section: Prevention and Non-pharmacological And Pharmacological Treatmentioning
confidence: 99%
“…Anorexia nervosa (7,8) Athletic amenorrhea (9) Celiac disease (10) Cystic fibrosis (11) Diabetes (type I) (12) Hematologic thalassemia, sickle-cell anemia (13) Inflammatory bowel disease (14) Malignancy (15)(16)(17) Post transplantation (18) Renal failure (19) Rheumatologic disorders (20) …”
Section: Chronic Diseasementioning
confidence: 99%
“…in a child can result from inadequate gains of bone mineral, bone loss, or a combination of the two (8,58,59). Understanding this is critical, because most drugs used to treat osteoporosis in adults are anticatabolic agents that reduce bone loss.…”
Section: Interpreting Low Bone Massmentioning
confidence: 99%